Aplikasi Tanya Jawab Ustadz Bebasis Web dengan Menggunakan Codiegniter: Introduction - Baqi, Alif Abdul; Dzikrul Hakim, Rafly; Muchlis; Fajri, Annur (LPPM STMIK ANTAR BANGSA, 2025)
The web-based Ustadz Question and Answer application is the use of a platform to develop applications that can be accessed anytime and anywhere, making it easier for users to get answers to religious questions that have been received by the ustadz or clerics from trusted and competent sources. The development methodology includes the use of CodeIgniter 3, Bootstrap 5, PHP, MySQL, and the Pusher library for real-time chat functionality. This application not only functions as a source of information, but also as a forum for interaction between the community and the ustadz through the online question and answer feature. The results of the study show that users can easily ask questions and get specific answers, thereby increasing their understanding of religious teachings. In addition, you can access a variety of learning materials such as articles, videos, and audio lectures, allowing for flexible learning. The study concluded that the Tanya Ustadz web-based application can effectively address the challenges faced by the Muslim community in finding valid religious information, while providing discussion capabilities to communities that support Ukwa Islamiyah. This application has the potential to increase community participation in understanding Islamic teachings and addressing social problems through proper religious guidance.